Engineering Investigation of a Deepwater Turret Mooring Suction Pile Inverse Catenary Based on BV and DNVGL Rules - Xuanze Ju, Zili Li, Baohui Dong, Jianghong Wang, Xianwu Meng (Forest Chemicals Review, 1970)
FPSO is the key unit of deepwater oilfield development, but it needs to be highly reliable to resist the extreme offshore environment. In order to get a reliable engineering system, the engineering investigation of mooring suction pile inverse catenary is conducted. Base on the seabed data and its soil mechanics, a complete engineering mechanical model for inverse catenary of suction pile is established, in the meanwhile, proposed a mooring slack calculation method. The engineering of the inverse catenary and mooring slack was evaluated based on the mooring load conditions classified by BV and DNVGL requirements, the seabed loads derived from mooring analysis results. The investigation results show that in the design and checking conditions, the tension range of the suction pile inverse catenary of this FPSO mooring is 10254kN~14075kN, the lug load angle range is 16.2°~30.1°, and the horizontal projection distance of the embedded chain range is 47.33m~80.30m. It can also be seen that the calculation results of BV rule and DNV rule are relatively close, the results based on different rules are mutually verified. The calculated slack (movement of chain along seabed from pretension to max intact load) is expected to be in the range 2.3 m - 0.4 m dependent on soft or stiff soil conditions and on installation (pretension) load. The final results were applied in the most deepwater FPSO project in the South China Sea with a depth of 420 meters.